The effect of psychoeducation on pregnant women’s understanding of the role of self-compassion in mental health - Nada Nabila; Farah Adibah Ibrahim (Universitas Trunojoyo Madura, 2026)
Pregnant women are a vulnerable group at risk of experiencing psychological disorders including depression, anxiety and stress, due to physical and emotional changes during pregnancy. This study aimed to examine the effectiveness of self-compassion-based psychoeducation in enhancing pregnant women's understanding of the importance of maintaining mental health during antenatal period. This research utilised a quasi-experimental design with a one-group pretest–posttest framework. A total of 10 pregnant women were recruited through purposive sampling according to predetermined inclusion criteria. The psychoeducation intervention was delivered through multimodal visual methods, comprising material presentations, interactive discussions, leaflet distribution, and quizzes to foster active participant engagement. To assess participants’ understanding of the psychoeducational material regarding the role of self-compassion in improving mental health during pregnancy, a questionnaire was administered at both the pretest and posttest stages. Data were analysed using descriptive statistic and a Paired Samples T-Test via SPSS software. The results showed a significant increase in understanding, with t (9) = -6.000 and p = 0.000 (p 0.05). These findings suggest that pregnant women developed a better understanding of the importance of self-compassion in supporting mental health after engaging in the psychoeducation session. The results of this study are expected to be widely implemented in primary maternal healthcare services and to inform further research development.